2008
DOI: 10.1128/jvi.01197-07
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Specific Genomic Markers Associated with Primary Hepatomas, Based on Complete Genomic Sequencing of Hepatitis B Virus

Abstract: We aimed to identify genomic markers in hepatitis B virus (HBV) that are associated with hepatocellular carcinoma (HCC) development by comparing the complete genomic sequences of HBVs among patients with HCC and those without. One hundred patients with HBV-related HCC and 100 age-matched HBV-infected non-HCC patients (controls) were studied. HBV DNA from serum was directly sequenced to study the whole viral genome. Data mining and rule learning were employed to develop diagnostic algorithms. An independent coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 30 publications
1
40
2
Order By: Relevance
“…Another study reported a nucleotide mutation related to HCC at nt.1165 in genotype B. (24) Although our study also found a greater number of nucleotide mutations in the HCC group (LC vs LC-HCC, 2 vs 6), the difference was statistically insignificant. The difference in the genotype is probably responsible for the different results, but a further study with more subjects is needed.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Another study reported a nucleotide mutation related to HCC at nt.1165 in genotype B. (24) Although our study also found a greater number of nucleotide mutations in the HCC group (LC vs LC-HCC, 2 vs 6), the difference was statistically insignificant. The difference in the genotype is probably responsible for the different results, but a further study with more subjects is needed.…”
Section: Discussioncontrasting
confidence: 52%
“…It is possible for nucleotide mutations to occur at the same site, but their functions differ for each genotype. (24) These results suggest that the viral genotype, HBx expression levels, and underlying conditions of the host are important for hepatocarcinogenesis. Thus, further study is required to elucidate the correlation between hepatocarcinogenesis by HBV and the expression of HBx in similar conditions.…”
mentioning
confidence: 82%
“…HBeAg expression and high viral load are associated with an increased risk of HCC (18,19). Some mutations in the PreS and the EnhII/BCP/Precore regions have been associated with the development of HCC (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Our recent meta-analysis using published data up to August 31, 2008 has shown that HBV PreS mutations, C1653T, T1753V, and A1762T/G1764A, are associated with an increased risk of HCC (30).…”
Section: Introductionmentioning
confidence: 99%
“…In Mainland China, an endemic area with almost one third of the HBsAg carriers found worldwide (1), HBV genotypes and mutations have been investigated in a limited number of the hospital-based patients and selected geographic areas (21,22,24,25,27,31,32). However, no community-based epidemiologic study with sufficient participants has shown nationwide distribution of HBV genotypes and the prevalence of the HCC-associated viral mutations as well.…”
Section: Introductionmentioning
confidence: 99%
“…HBV genotypes have distinct geographic distributions and have been shown to differ with regard to clinical liver diseases, outcomes, and responses to interferon treatment (5). In East Asia, where HBV genotypes B and C are endemic, viral factors of HBV, including genotype C infection, hepatitis B virus e antigen (HBeAg) expression, high viral load (Ͼ10 4 copies/ml), and mutations in the enhancer II/basal core promoter/precore (EnhII/BCP/PC) and the pre-S regions, as well as active hepatic inflammation contribute greatly to the development of advanced liver diseases, especially HCC (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Some of the mutations can happen years before a diagnosis of HCC is made and gradually accumulate during the progression of chronic liver diseases (9,(13)(14)(15)(16).…”
mentioning
confidence: 99%